Microbial Pack as Probiotic Supplements to Improve Gut Immunity for Homeostasis - Siddiqui, Nadeem (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Probiotics are live microorganisms that, when administered or present in sufficient quantities, have beneficial effects on host health in increased lifespan. Probiotic supplements must be tested to determine their efficacy as a non-chemical approach to promoting health and well-being. Objective: Our research work focuses on determining the molecular impact of probiotic administration on homeostasis and immunity. Methods: Shrimpswere administered with recommended doses of microbial pack containing Bacillus species and Rhodococcus species and the fermentation was carried at 37Â°C for 72 h under microaerophilic condition. The parameters such as pH, microbial load, acidity, and concentration of reducing sugar had been measured. Results: This probiotic pack when used either alone or in combination with traditional dairy starter, significantly improved the nutritional properties and the shelf life of the product. Conclusion: The current work will be useful in developing novel functional foods based on these unique probiotic properties.